Abnormal Typical Pattern of Platelet Function and Thromboxane Generation in Unstable Angina - Zahavi, M; Zahavi, J; Schafer, R; Firsteter, E; Laniado, S (Thrombosis and Haemostasis, 1989)
Platelet aggregation (PA), platelet thromboxane B2 (TXB2) generation and 14C 5-hydroxytryptamine (5HT) release were studied in 13 patients with unstable angina, and compared to 14 patients with stable angina and 16 healthy controls. A typical pattern, distinct in 4 aspects from stable angina patients or controls, was observed in the unstable angina patients. ADP or collagen induced shape change was 3-4 times greater, the extent of epinephrine induced PA was nil or very low, the extent of collagen induced 14C 5HT release was also reduced while collagen induced platelet TXB2 generation was increased in spite of a reduced extent of PA. The extent of ADP or collagen induced PA was also significantly reduced. These results indicate a platelet membrane abnormality occurring presumably during contact of the circulating platelets with a non-occlusive thrombus observed at sites of ruptured plaques in unstable angina patients. Since also the pattern (20-30% overlap with control values) was distinct from that of stable angina patients, it might indicate an active thrombotic process.Plasma β-thromboglobulin (βTG) and TXB2 levels and serum TXB2 generation were also studied in the cardiac patients and controls and in another 10 patients with advanced peripheral occlusive arterial disease (POAD). Plasma βTG and TXB2 levels were slightly elevated in the unstable angina patients and markedly elevated in the POAD patients. Serum TXB2 generation was, however, elevated in the stable angina patients (p <0.002) and more so in the unstable angina patients (p <0.001) compared to controls or to POAD patients. This was presumably mediated through enhanced thrombin generation. These results suggest that the measured plasma βTG variable in the unstable angina patients is not useful in the assessment of in vivo platelet activation. It is presumably reflecting the sum of local enhanced platelet activation (at sites of ruptured plaques) and of reduced function of the “defective” circulating platelets. The ability of the platelets of unstable angina patients to generate large amounts of TXB2 if occurring in vivo might induce an intense coronary vasospasm.
Keywords: Unstable angina; Thromboxane generation; Thrombosis